1992
DOI: 10.1007/bf01066763
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring adult psychiatric practices to the field of geriatrics

Abstract: The United States' population is aging. Epidemiological surveys suggest significant rates of mental illness amongst the rapidly growing over-65 cohort. A burgeoning experience and data base related to the developing sub-discipline of geriatric psychiatry is now available. This article synthesizes key issues and concepts as an introduction to geropsychiatric practice-in particular, a) the interface between medical illness and psychiatric expression in the elderly, b) delirium, c) dementia, and d) depression-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…This is in line with more recent epidemiological studies that report a proportion of 0.5-1% of old age bipolar I and II patients [7,8]. Even higher numbers have been observed in special settings, e.g., a prevalence of 3-10% in nursing homes [9,10]. Dols and colleagues [11] report a 6% prevalence of manic episodes in elderly psychiatric inpatients, with 44% having late onset mania.…”
Section: Introduction: Epidemiology Of Bipolar Disorder In Old Age Patientssupporting
confidence: 76%
“…This is in line with more recent epidemiological studies that report a proportion of 0.5-1% of old age bipolar I and II patients [7,8]. Even higher numbers have been observed in special settings, e.g., a prevalence of 3-10% in nursing homes [9,10]. Dols and colleagues [11] report a 6% prevalence of manic episodes in elderly psychiatric inpatients, with 44% having late onset mania.…”
Section: Introduction: Epidemiology Of Bipolar Disorder In Old Age Patientssupporting
confidence: 76%
“…Samples that do not include elderly individuals living in nursing homes or state residential and assisted living facilities may underestimate the number meeting criteria for mania. One study estimated the prevalence of mania in nursing home residents to be as high as 10% [3] compared with the 1% to 2% prevalence in the general adult population.…”
Section: Introductionmentioning
confidence: 97%
“…It has been estimated that 10% of new-onset mania cases occur in patients over 50 years of age (Kaplan and Sadock, 1985) and that bipolar disorder accounts for 5% to 19% of mood disorder presentations in the elderly (Cassano et al, 2000). Wylie et al (1999) reported that approximately 7% of geriatric inpatient admissions were for bipolar illness, while the Epidemiologic Catchment Area study in 1990 found that 9.7% of all nursing home patients had bipolar disorder (Greenwald et al, 1992).…”
mentioning
confidence: 99%